2007
DOI: 10.1098/rspb.2006.0347
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control in active sensing: rat exploratory whisking is modulated by environmental contact

Abstract: Rats sweep their facial whiskers back and forth to generate tactile sensory information through contact with environmental structure. The neural processes operating on the signals arising from these whisker contacts are widely studied as a model of sensing in general, even though detailed knowledge of the natural circumstances under which such signals are generated is lacking. We used digital video tracking and wireless recording of mystacial electromyogram signals to assess the effects of whisker-object conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
297
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 251 publications
(331 citation statements)
references
References 45 publications
27
297
0
1
Order By: Relevance
“…As previously reported [19], the interaction between this excitation and this suppression often leads to rapid periodic interaction with the surface (something like 'tapping') by contacting whiskers (this can be seen in some of the supplementary videos). This mix of excitatory and inhibitory influences may be a useful model of rat behaviour [34], and may act to maximize the number of contacts that occur whilst normalizing the depth of those contacts. The whisker movement that results during tracking has reduced amplitude and more protracted average angle, these being the main features described by Munz et al [23] and Berg et al [28].…”
Section: Controlmentioning
confidence: 99%
“…As previously reported [19], the interaction between this excitation and this suppression often leads to rapid periodic interaction with the surface (something like 'tapping') by contacting whiskers (this can be seen in some of the supplementary videos). This mix of excitatory and inhibitory influences may be a useful model of rat behaviour [34], and may act to maximize the number of contacts that occur whilst normalizing the depth of those contacts. The whisker movement that results during tracking has reduced amplitude and more protracted average angle, these being the main features described by Munz et al [23] and Berg et al [28].…”
Section: Controlmentioning
confidence: 99%
“…Second, behavioral data obtained by Carvell and Simons [10], in animals that were trained to discriminate texture for reward using only their macrovibrissae, provides evidence of an "active touch" strategy [25] that rats may use to optimise their texture discrimination capabilities. Specifically, they observed that while some of the longer, more caudal, macrovibrissae were whisked back and forth across the target surface, presumably to obtain texture-related information, a number of the smaller rostralmost hairs remained in a "relatively motionless, protracted state [...] never losing contact with the surface" (p. 2641).…”
Section: Discussionmentioning
confidence: 98%
“…Inhibitory and excitatory projections from the strain sensors at the base of each whisker would modulate the behaviour of the pattern generators when contacts were made with the environment, thus affecting the drive signals to the BioMetal wires. This feedback control system was adopted as it best fits both anatomical (no proprioception in mystacial musculature [14]) and ethological observations (contact mediated adaptation [24]) of rats. For further details of the robot whisker morphology, actuation, and transductions mechanisms see [26], [29].…”
Section: Artificial Whisker Systemmentioning
confidence: 99%
“…A common form of contact-related modulation, observed in multiple species [7,38], is that whisker protraction is controlled following a unilateral contact, such that whiskers on the side of the snout ipsilateral to the contact are reined in and those on the contralateral side brought forward, sometimes contacting another part of the encountered obstruction and resulting in bilateral contact. We refer to this observation as contact-induced asymmetry (CIA, [7]).…”
Section: Introductionmentioning
confidence: 99%